Methylprednisolone Therapy in Acute Hemorrhagic Edema of Infancy. (5th March 2014) - Risikesan, Jeyanthini; Koppelhus, Uffe; Steiniche, Torben; Deleuran, Mette; Herlin, Troels
Abstract : We present a case of an 18-month-old boy who showed severe clinical signs indicative of acute hemorrhagic edema of infancy (AHEI) with painful purpuric skin affection primarily of the face and marked edema of the ears. The histological findings were diagnostic for leukocytoclastic vasculitis and thus met the histological criteria for AHEI. Indicative of infection as causative agent for the condition were symptoms of gastroenteritis. High-dose intravenous corticosteroids led to a fast resolution of symptoms and normalization of laboratory parameters. AHEI is usually not described as being very responsive to corticosteroids. The case presented here indicates that severe cases of AHEI can be treated with high-dose intravenous corticosteroids resulting in significant relief and shortening of the symptoms. Clinical followup showed no underlying malignancy or other severe chronic systemic diseases thus confirming earlier reports that AHEI is not associated with such conditions. The differential diagnoses with AHEI are discussed.